1999
DOI: 10.1073/pnas.96.26.15062
|View full text |Cite
|
Sign up to set email alerts
|

The human natural killer cell immune synapse

Abstract: N atural killer (NK) cells express a variety of inhibitory killer Ig-like receptors (KIR) that inhibit cytotoxicity upon recognition of class I MHC proteins (1). In this manner NK cells detect diseased cells through their loss of expression of self-MHC protein rather than by directly detecting foreign antigen, a conjecture known as the missing self-hypothesis (2). Inhibitory NK receptors containing two Ig domains, denoted KIR1 (or KIR2DL1) and KIR2 (or KIR2DL2), recognize the class I MHC proteins, HLA-Cw4 or -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
437
3
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 384 publications
(460 citation statements)
references
References 37 publications
17
437
3
3
Order By: Relevance
“…This model would explain the spontaneous ATP-independent segregation of proteins observed at the iNKIS. 29,33 The CD94-T4 protein is 21 amino acids shorter than the full-length CD94. Its preferred partner is NKG2B, which is 18 amino acids shorter than NKG2A.…”
Section: Multiple Transcripts Of Cd94mentioning
confidence: 99%
“…This model would explain the spontaneous ATP-independent segregation of proteins observed at the iNKIS. 29,33 The CD94-T4 protein is 21 amino acids shorter than the full-length CD94. Its preferred partner is NKG2B, which is 18 amino acids shorter than NKG2A.…”
Section: Multiple Transcripts Of Cd94mentioning
confidence: 99%
“…After specific ligand engagement, cytolytic cells bind to sensitive target cells and rapidly reorganize cell membrane proteins, accumulating actin, talin and lytic granules at the cell-cell contact site (immunological synapse) [2,3]. Serine proteases (granzymes) and membrane-perturbing proteins, perforins (PFN) and granulysins are then released at the immunological synapse to induce target cell death [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In T cells these proteins often interact with other proteins with two IgSF domains in an end-to-end topology. For these interactions to occur, the opposing cell membranes need to come into close proximity and the size of the interacting proteins has been shown to be important in the formation of the immunological synapse and triggering of T cells [10][11][12]. Mutagenesis analysis of CD200 indicated that the N-terminal (membrane-distal) domain of CD200 contains the CD200R binding site [13].…”
Section: Introductionmentioning
confidence: 99%